Examining knowledge gap and psychic distance paradox interdependence: An exploratory inquiry - Symeon Mandrinos; Nik Malini Nik Mahdi (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to examine the relationship between the Knowledge Gap (KG) and Psychic Distance Paradox and to explain the three dominant factors; experiential knowledge, information and learning myopia. Design/methodology/approach – The paper uses an inductive multiple case study methodological approach. Findings – This research found that the KG has an interdependent relationship with the Psychic Distance Paradox; however, this interdependence does not exist in isolation; rather there is a distinct “time-continuum” nexus running through and enveloping these two theoretical frameworks and the three factors of experiential knowledge, information and learning myopia. Research limitations/implications – This paper provides a deeper understanding to the existing body of knowledge on the relationship between theKGand Psychic Distance Paradox and the emerging factors. Originality/value – This study is the first to examine the interdependence between the three factors of experiential knowledge, information and learning myopia and KG and Psychic Distance Paradox. This examination provides new ideas to practitioners and researchers relating to the advancement of export process in neighbour countries.